A Clinical Study of Cumulative Effect of Shwadanstradi Tail Manyabasti and Nasya in the Management of Manyastambha with special reference to Cervical Spondylitis - Pooja Chheniya; Lalit R Kukde; Sonal D Wankhede (International Journal of Ayurveda and Pharma Research, 2025)
Manyastambha is a clinical condition of the neck region and is one of the prone disorders caused by vitiated Vata in working mid-aged population. Acharya Charak describes Manyastambha in eighty Nanatamaj vatavyadhis. However, As per modern science, Manyastambha can be correlated to cervical spondylosis. It is a common health problem encountered in practice whose prevalence increases with age, and is estimated to be around 95% by age 65. In this single arm pre-post experimental clinical study, without regard to sex, religion, or other factors, a total of 30 individuals with the defining signs and symptoms of Manyastambha were chosen for this research trial (cervical spondylitis). In the current study, Shwadanstradi Tail Manya Basti and Nasya as described by Acharya Charak in Chikitsa sthana were administered for 14 days, with a regular follow up of 8th, 14th and 21st days respectively without any internal medications and alteration in diet and lifestyle. Results showed that pain was reduced by 79.33% (VAS Scale), Stambha/stiffness 57.47%, and total neck mobility by 56.44% which were statistically significant. Statistically very significant results were also found in neck flexion (64.13%), neck extension (52.38%) and passive neck flexion (52.27%). Thus, conservative cumulative management of Manyabasti and Nasya of Shwadanshtradi Tail for a specific period when administered with proper duration dose and time relieves the clinical signs and symptoms of Manyastambha (cervical spondylitis) along with no side effects. Shwadanstradi Tail in the Matra of 100ml for Basti and 1 Bindu (8 drops) for Nasya found to reduce pain, neck stiffness, tenderness, radiation of pain and numbness.